2022
DOI: 10.1016/j.esmoop.2021.100355
|View full text |Cite
|
Sign up to set email alerts
|

First-line immunotherapy in advanced non-small-cell lung cancer patients with ECOG performance status 2: results of an International Expert Panel Meeting by the Italian Association of Thoracic Oncology

Abstract: Background Immunotherapy represents the standard of care in the first-line treatment of advanced non-small-cell lung cancer (NSCLC), either as monotherapy in high programmed death-ligand 1 (PD-L1)-positive tumors (≥50%) or in combination with platinum-based chemotherapy regardless of PD-L1 status. However, most pivotal clinical trials of immune checkpoint inhibitors (ICIs) did not include patients with Eastern Cooperative Oncology Group (ECOG) performance status (PS) 2. Hence, a consensus is lacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 46 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…Recently, the results of an International Expert Panel Meeting supported the safety of immunotherapy, but not immunochemotherapy, in NSCLC patients with PS 2, based on clinical evidence (24). In the KEYNOTE-042 study, irAEs were reported to be 63% at any grade and 18% at grade 3 or higher in the pembrolizumab group of NSCLC patients with good PS (5).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the results of an International Expert Panel Meeting supported the safety of immunotherapy, but not immunochemotherapy, in NSCLC patients with PS 2, based on clinical evidence (24). In the KEYNOTE-042 study, irAEs were reported to be 63% at any grade and 18% at grade 3 or higher in the pembrolizumab group of NSCLC patients with good PS (5).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, despite questionnaires reporting quality of life are currently considered to be of high quality, there are currently no international guidelines for statistical analysis of QOL in cancer patients using ICIs, and there is still a lack of confirmation of research hypotheses and questionnaires in cancer patients treated with ICIs in methodological aspects [ 33 ]. ECOG PS ≥ 2 was almost excluded from clinical trials, and future studies should be focused on older and weak patients [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over half of our real-world ES PS population had an ECOG PS of ≥2 at diagnosis. While chemotherapy and ICI treatments have been widely used in good PS patients with lung cancer, due to the evidence in NSCLC, the feasibility is much less clear in PS 2 patients and is not currently informed by randomized clinical trials ( 16 ). A prospective randomized phase II clinical trial of ICIs with or without carboplatin and paclitaxel in advanced NSCLC with PS 2 is yet to be reported ( 17 ).…”
Section: Discussionmentioning
confidence: 99%